PIROLISIS SERBUK KAYU ULIN (Eusideroxylon zwageri) DENGAN INSTRUMEN PYROLYSIS-GAS CHROMATOGRAPHY-MASS SPECTROSCOPY - Sri Astika Putri; RR Dirgarini Julia Nurlianti Subagyono; Rahmat Gunawan (PROSIDING SEMINAR KIMIA, 2022)
Pyrolysis of Ulin sawdust (Eusideroxylon zwageri) with pyrolysis-gas chromatography-mass spectroscopy (Py-GC/MS) instrument haw been performed. This study was conducted to determine the chemical composition resulting from the pyrolysis process of Ulin sawdust (Eusideroxylon zwageri) using the Py-GC/MS instrument. Pyrolysis was performed at a temperature of 350 oC, 450 oC and 550 oC under the flow of helium gas (He). The chemical composition of the product resulting from the pyrolysis process of Ulin sawdust was lignin derivative products of 56-73%, cellulose/hemicellulose derivative products of 17-22%. The pyrolysis products with the highest per cent were Phenol,4-ethenyl-2,6-dimethoxy-; .beta.-D-Glucopyranose,1,6-anhydro; and isoelemicin. Keywords: Pyrolysis, Eusideroxylon zwageri, Py-GC/MS